Phosphoryl guanidine oligonucleotides as primers for RNA-dependent DNA synthesis using murine leukemia virus reverse transcriptase - E. S. Dyudeeva; I. A. Pyshnaya (Вавиловский журнал генетики и селекции)
Modern approaches to the detection and analysis of low-copy-number RNAs are often based on the use of RNA-dependent DNA polymerases, for example, in reverse-transcription PCR. The accuracy and efficiency of cDNA synthesis in the reverse-transcription reaction catalyzed by reverse transcriptase (RNA-dependent DNA polymerase) significantly affect the correctness of the results of PCR diagnostic assays and/or RNA sequencing. In this regard, many studies are focused on the optimization of the reverse-transcription reaction, including the search for more perfect primers necessary to obtain a full-length DNA copy of RNA under study. The best-known completely uncharged analogs of oligonucleotides – morpholine oligonucleotides and peptide nucleic acids – cannot be substrates for enzymes that process nucleic acids. The aim of this work was to conduct a pilot study of uncharged phosphoryl guanidine oligodeoxyribonucleotides (PGOs) as primers for mouse leukemia virus reverse transcriptase (MMLV H-). Specific features of elongation of partially and completely uncharged PGO primers were investigated. It was demonstrated that PGOs can be elongated efficiently, e.g., in the presence of a fragment of human ribosomal RNA having complex spatial structure. It was shown that the proportion (%) of abortive elongation products of a PGO primer depends on buffer ionic strength, nucleotide sequence of the primer, and the presence and location of phosphoryl guanidine groups in the primer. The results indicate the suitability of PGOs, including completely electroneutral ones, as primers for reverse-transcription PCR, thereby opening up new prospects for the creation of experimental models for the analysis of highly structured RNA.